1994
DOI: 10.1016/0014-5793(94)80553-9
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein is saturable by pro‐oxidant copper

Abstract: The oxidative resistance of low density lipoprotein (LDL) can be experimentally described by the length of time during which no significant lipid peroxidation is observed in a pro-oxidant environment. This period of inhibited oxidation, termed the 'lag phase', is partially due to the radical scavenging reactions of the anti-oxidants contained in the LDL particle. We have shown that the LDL lag time decreases with increasing copper concentration, leveling out at a relatively high copper-to-LDL ratio. This behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(120 citation statements)
references
References 24 publications
7
111
0
2
Order By: Relevance
“…The aliquots of plasma were stored at 780 C for a maximum of three months. Plasma samples were thawed and LDL was isolated by ultracentrifugation using a singlestep discontinuous gradient in a Beckman NVT 65 rotor at 60 000 rpm for 2 h at 10 C (Gieseg & Esterbauer, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…The aliquots of plasma were stored at 780 C for a maximum of three months. Plasma samples were thawed and LDL was isolated by ultracentrifugation using a singlestep discontinuous gradient in a Beckman NVT 65 rotor at 60 000 rpm for 2 h at 10 C (Gieseg & Esterbauer, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the physiological relevance of the in vitro LDL oxidation assay is still a matter of debate, eg due to the unphysiologically high Cu þ -concentrations that are applied. Readers are referred to method papers for further discussions (Giesig & Esterbauer, 1994;Yoshida et al, 1994;Abuja & Albertini, 2001). …”
Section: Preparation and Oxidation Of Ldlsmentioning
confidence: 99%
“…2a). Kinetic parameters were further elaborated according to Gieseg and Esterbauer [10], who recently showed that the relationship between Gg and Cu 2+ concentration can be quantitatively described by the following equation which has the same functional form as the Michaelis and Menten equation:…”
Section: Resultsmentioning
confidence: 99%
“…The value of K was given by the negative reciprocal of the x-axis intercept and the value of tmi,, by the ),-axis intercept [10]. K value resulted 1.2/~M Cu 2+ in the absence of HE and 2.5 tiM Cu 2+ in the presence of 150 /.tg/ml HE.…”
Section: Resultsmentioning
confidence: 99%